Proceedings of the 11th Working Conference on Mining Software Repositories 2014
DOI: 10.1145/2597073.2597076
|View full text |Cite
|
Sign up to set email alerts
|

The impact of code review coverage and code review participation on software quality: a case study of the qt, VTK, and ITK projects

Abstract: Software code review, i.e., the practice of having third-party team members critique changes to a software system, is a well-established best practice in both open source and proprietary software domains. Prior work has shown that the formal code inspections of the past tend to improve the quality of software delivered by students and small teams. However, the formal code inspection process mandates strict review criteria (e.g., in-person meetings and reviewer checklists) to ensure a base level of review quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
184
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 274 publications
(204 citation statements)
references
References 40 publications
5
184
1
Order By: Relevance
“…We found that from 374 reviews 6 created on 23/12/2011, there are 356 reviews (98%) that were abandoned on 29/12/2010. Moreover, these reviews were created by the same developer at consecutive times.…”
Section: Q1mentioning
confidence: 90%
See 1 more Smart Citation
“…We found that from 374 reviews 6 created on 23/12/2011, there are 356 reviews (98%) that were abandoned on 29/12/2010. Moreover, these reviews were created by the same developer at consecutive times.…”
Section: Q1mentioning
confidence: 90%
“…Extracting knowledge from these datasets has produced promising research with the goal of improving the software quality and software development process. Recently, many studies have used code review datasets to understand and improve both review effort [2]- [5] and review quality [6], [7]. However, a raw code review dataset is generally imperfect since the data collection process in each support tool 1 https://code.google.com/p/gerrit/ 2 https://www.reviewboard.org/ 3 https://code.google.com/p/rietveld/ varies in methodology, accuracy, and degree of automation [8].…”
Section: Introductionmentioning
confidence: 99%
“…Stewart et al [12] tried to relate code quality to factors such as release frequency, number of releases and the changes in size of the code base across releases in open source software projects, but could not derive any conclusions. McIntosh et al [13] studied the impact of code review coverage on software quality. Baccelli and Bird [14] investigated the outcomes and challenges of modern tool-based code reviews and observed that, amongst other things, code reviews are not only used for revealing defects, but also serve to promote awareness and knowledge transfer.…”
Section: Related Workmentioning
confidence: 99%
“…al. [4] summarized their case study with statement: "Components with higher review coverage tend to have fewer post-release defects". Their analysis also indicates that "Although review coverage is negatively associated with software quality in our models, several defect-prone components have high coverage rates, suggesting that other properties of the code review process are at play."…”
Section: Introductionmentioning
confidence: 99%